Implementsi Model Project Based Learning Dalam Mata PelajaranPendidikan Agama Islam Di SMA Darut Taqwa Purwosari Pasuruan - Sayyid Agil Syirot (4, 2025)
This study aims to describe the implementation of the Project-Based Learning (PjBL) model in Islamic Religious Education (PAI) learning at Darut Taqwa High School in Purwosari, Pasuruan. The PjBL model was chosen as an innovative approach capable of increasing active student engagement, strengthening understanding of Islamic values, and shaping noble character through contextual and applicable learning activities. This study used a qualitative approach with descriptive methods. Data collection techniques were conducted through observation, in-depth interviews, and documentation. The research informants consisted of PAI teachers, the principal, and students. The results showed that the implementation of the PjBL model began with planning learning projects aligned with core competencies and learning objectives, such as the creation of Islamic religious videos, social campaigns, and Islamic wall magazines. The activities were implemented collaboratively, with students working in small groups and actively involved in the design process, from project design to evaluation. The evaluation was comprehensive, encompassing cognitive, affective, and psychomotor aspects. The positive impact of PjBL implementation was seen in increased student learning motivation, critical thinking skills, creativity, and strengthening of Islamic character. Thus, the Project-Based Learning model has proven relevant and effective in Islamic Religious Education (PAI) teaching, as an effort to shape a generation that is knowledgeable, moral, and ready to face life's challenges based on Islamic values. Abstrak Penelitian ini bertujuan untuk mendeskripsikan implementasi model Project Based Learning (PjBL) dalam pembelajaran Pendidikan Agama Islam (PAI) di SMA Darut Taqwa Purwosari Pasuruan. Model PjBL dipilih sebagai pendekatan inovatif yang mampu meningkatkan keterlibatan aktif siswa, memperkuat pemahaman terhadap nilai-nilai keislaman, serta membentuk karakter mulia melalui kegiatan pembelajaran yang kontekstual dan aplikatif. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi. Informan penelitian terdiri dari guru PAI, kepala sekolah, dan peserta didik. Hasil penelitian menunjukkan bahwa implementasi model PjBL diawali dengan perencanaan proyek pembelajaran yang disesuaikan dengan kompetensi dasar dan tujuan pembelajaran, seperti pembuatan video dakwah, kampanye sosial, dan majalah dinding Islami. Pelaksanaan kegiatan berlangsung secara kolaboratif, di mana siswa bekerja dalam kelompok kecil dan terlibat aktif dalam proses perancangan hingga evaluasi proyek. Evaluasi dilakukan secara menyeluruh mencakup aspek kognitif, afektif, dan psikomotorik. Dampak positif dari implementasi PjBL terlihat pada peningkatan motivasi belajar siswa, kemampuan berpikir kritis, kreativitas, dan penguatan karakter Islami. Dengan demikian, model Project Based Learning terbukti relevan dan efektif diterapkan dalam pembelajaran PAI sebagai upaya membentuk generasi yang berilmu, berakhlak, dan siap menghadapi tantangan kehidupan dengan berlandaskan nilai-nilai Islam.